Spatial Politics and a Native American Reservation: Reading Red Power: A Graphic Novel with Author Brian Wright-McLeod - Kristina Aurylaite (European Journal of American Studies)
This paper discusses Dakota-Anishinabe Brian Wright-McLeod’s graphic novel Red Power (2011), which tells a story of land conflict surrounding a Native American reservation and of a group of Native activists involved in it. Based on an interview with Wright-McLeod and with several references to Jason Aaron and R.M Guéra’s reservation-based graphic novel Scalped (2007-2012), it focuses on the politics of space and identity. Drawing on propositions from cultural geography about the interdependency of social and spatial structures and their mutually constitutive relationship, the paper analyzes how Red Power makes use of the visual aspect of the graphic novel to rearticulate the colonizer-colonized dichotomy of identity politics and expose the mechanisms through which power structures continue to restrict, disrupt, and exploit indigenous spaces. The paper then proceeds to examine how the novel seeks out possibilities of unsettling the spatial order imposed upon indigenous people by focusing on resistance organized by Native activists. It also explores how the novel suggests ways of experiencing and being in space that escape both colonial ways of knowing and conceiving it and, more importantly, colonial control over it.